Green Synthesis of Carbon Dots Derived from Walnut Oil and an Investigation of Their Cytotoxic and Apoptogenic Activities toward Cancer Cells - Elham Arkan; Ali Barati; Mohsen Rahmanpanah; Leila Hosseinzadeh; Samaneh Moradi; Marziyeh Hajialyani (Advanced Pharmaceutical Bulletin, 2018)
Purpose: This paper introduces a green and simple hydrothermal synthesis to prepare carbon quantum dots (CQDs) from walnut oil with a high quantum yield. In addition, cytotoxic and apoptogenic properties of the CQDs were analyzed on human cancer cell lines. Methods: The optical properties and morphological characteristic were investigated by the TEM, XRD, FT-IR, UV-vis and photoluminescence (PL).The cytotoxic potential of walnut CQDs was evaluated on PC3, MCF-7 and HT-29 human carcinoma cell lines using the MTT methods. The mechanism of action was studied by investigating the mode of cell death using the activation of caspase-3 and 9 as well as mitochondrial membrane potential (MMP). Cellular uptake of the CQDs was detected by fluorescence microscope. CQDs had an average size of 12 nm and a significant emission at 420 nm at an excitation wavelength of 350 nm was recorded. Results: The prepared CQDs possessed a good fluorescent quantum yield of 14.5% with quinine sulfate (quantum yield 54%) as a reference and excellent photo as well as pH stabilities. The walnut CQDs were proved to be an extremely potent cytotoxic agent, especially against MCF-7 and PC-3 cell lines. Induction of apoptosis by CQDs was accompanied by an increase in the activation of caspase-3. Caspase-9 activity did not increase after exposure to the CQDs. Additionally; the MMP did not show any significant loss. Conclusion: The results of our study can corroborate the cytotoxic and apoptotic effect of walnut CQDs in the PC3 and MCF-7 cancer cell lines.